ANTROPONIMIC MODEL: ABOUT NESSESARITY OF NATIONAL SURNAME (Scientific journal of the Fergana State University, 2024)
In this article were particularly analyzed some questions such as history, evolution, motives of formation, territorial features and ethimology of our national surnames. Some presumption were given by author also specialist’s ideas and considerations about these problems were studied.The proposed recommendations and predictions are sketchy forms of national surnames and may be subject to change and additions over time. Furthermore, in process of searching historical sources, legal and regulatory documents relating to sphere werestudied as well as well-known toponimysts’ scientific workswere used.